(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Magnetic Resonance Imaging (MRI) is a non-invasive diagnostic technique widely used in medical imaging to produce high-resolution anatomical and functional images of the human body. This article explores the fundamental physical principles that underlie MRI technology, including nuclear magnetic resonance (NMR), the behavior of hydrogen nuclei in a magnetic field, radiofrequency (RF) excitation, and relaxation phenomena. Additionally, the roles of gradient magnetic fields and signal acquisition in image formation are examined. Understanding these physical mechanisms is crucial for optimizing image quality, ensuring patient safety, and advancing MRI-based diagnostic capabilities. This review aims to provide a comprehensive overview of the physics behind MRI, serving as a foundational resource for medical professionals, researchers, and students in the fields of radiology, biomedical engineering, and medical physics.